2002
DOI: 10.1002/1521-4141(200207)32:7<2046::aid-immu2046>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

T cell priming by dendritic cells: thresholds for proliferation, differentiation and death and intraclonal functional diversification

Abstract: The variables that influence priming of human naive CD4+ T cells by dendritic cells (DC) were dissected in vitro by analyzing the response to the bacterial superantigen toxicshock syndrome toxin or to alloantigens. We show that under conditions that force DC‐T cell interactions a single DC can prime up to 20 naive T cells. Moreover, the strength of antigenic stimulation, as determined by DC numbers, antigen dose, TCR avidity and duration of DC‐T cell interactions, drives the progressive differentiation of prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
82
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 53 publications
8
82
0
Order By: Relevance
“…The timing of contraction suggests that T cells sense the clearance of infection, then initiate the contraction phase, as survival cytokines become limiting (19, 49 -51). This model is consistent with the suggestion that a long period of Ag exposure, due to protracted clearance of infection, results in "fit" T cells that proliferate extensively and differentiate to longlived memory T cells, whereas a short exposure to Ag results in abortive T cell proliferation, and tolerance (52)(53)(54)(55)(56)(57). Both models predict that the duration of infection will determine the timing of the transition between contraction of Ag-specific T cells and the generation of memory.…”
Section: Discussionsupporting
confidence: 85%
“…The timing of contraction suggests that T cells sense the clearance of infection, then initiate the contraction phase, as survival cytokines become limiting (19, 49 -51). This model is consistent with the suggestion that a long period of Ag exposure, due to protracted clearance of infection, results in "fit" T cells that proliferate extensively and differentiate to longlived memory T cells, whereas a short exposure to Ag results in abortive T cell proliferation, and tolerance (52)(53)(54)(55)(56)(57). Both models predict that the duration of infection will determine the timing of the transition between contraction of Ag-specific T cells and the generation of memory.…”
Section: Discussionsupporting
confidence: 85%
“…In this system, CD70 costimulation particularly favored the responses of V␤2-negative T cells that are usually only minimally responsive to TSST. Langenkamp et al (27) have suggested that V␤2 Ϫ T cells responding to TSST represent low-affinity T cells. The system therefore allows for comparing high-affinity and low-affinity human T cell responses, which is otherwise not possible because of the low frequency of human T cells to nominal peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Mature dendritic cells (DC) were generated from PBMCs, as previously described (27). In brief, monocytes were isolated by either plastic adherence or anti-CD14 magnetic beads (Miltenyi Biotec), and were cultured for 6 days in RPMI 1640-10% FCS supplemented with 800 U/ml GM-CSF and 1000 U/ml IL-4 (both from R&D System).…”
Section: Cell Separationmentioning
confidence: 99%
“…In general, tolerance is initiated when DCs are immature, whereas the initiation of immunity requires an effective DC maturation signal. After reaching the lymph nodes, DCs present processed Ag to T cells via both classical (class I and II MHC) and nonclassical (CD1 family) pathways (24,31,32). In addition to their maturation status, DCs can be subdivided into a CD11c Ϫ (plasmacytoid DC) and a CD11c ϩ (myeloid DC) subset (20,33).…”
mentioning
confidence: 99%